Terahertz quantum cascade lasers with >1 W output powers. Issue 4 (1st February 2014) - Li, Lianhe; Chen, Li; Zhu, Jingxuan; Freeman, J.; Dean, P.; Valavanis, A.; Davies, A.G.; Linfield, E.H.
Abstract : Terahertz (THz) frequency quantum cascade lasers emitting peak powers of >1 W from a single facet in the pulsed mode are demonstrated. The active region is based on a bound‐to‐continuum transition with a one‐well injector, and is embedded into a surface‐plasmon waveguide. The lasers emit at a frequency of ∼3.4 THz and have a maximum operating temperature of 123 K. The maximum measured emitted powers are ∼1.01 W at 10 K and ∼420 mW at 77 K, with no correction made to allow for the optical collection efficiency of the apparatus.